Who uses Outdoor Fitness Equipment in Urban Spaces? User Profiles and Usage Patterns: A Scoping Review - Urbano, Mikel; Giakoni, Frano; Larrinaga-Undabarrena, Arkaitz; Río, Xabier; Coca, Aitor; Martínez-Santos, Raúl (Journal of Cultural Analysis and Social Change, 2025)
This scoping review aims to systematically map the available evidence on the use of outdoor fitness equipment (OFE) in urban spaces, identifying user profiles, usage patterns, contextual factors, barriers, and facilitators. The review followed the PRISMA-ScR guidelines, with the protocol registered in the Open Science Framework (osf.io/h2tz8). Searches were conducted in Web of Science and Scopus databases, including studies published between 2010 and 2025 in English or Spanish that directly observed the use of OFE in public settings. Ten studies met the inclusion criteria. Results show that OFE are primarily used by adults and older adults, with participation varying according to sex and cultural context. Usage is characterized by short, moderate-intensity sessions, most frequently in the morning and late afternoon, with greater attendance on weekends. Environmental and design factors—such as proximity, maintenance, shade, and complementary amenities—strongly influence participation levels. Reported barriers include poor maintenance, overcrowding, and lack of knowledge about correct use, whereas accessibility, safety, and social interaction act as key facilitators. Only one study assessed cost-effectiveness, revealing limited economic evidence. OFE are an accessible and low-cost strategy for promoting community physical activity, but their effectiveness depends on integration with broader urban health and mobility strategies. Future research should explore long-term impacts, economic feasibility, and the role of local governance and technical management in sustaining these facilities.